Effect of feeding Atlantic salmon ( Salmo salar L.) a diet enriched with stearidonic acid from parr to smolt on growth and n-3 long-chain PUFA biosynthesis - Codabaccus, Mohamed B.; Bridle, Andrew R.; Nichols, Peter D.; Carter, Chris G. (British Journal of Nutrition, 2011)
Vegetable oils (VO) have become the predominant substitute for fish oil (FO) in aquafeeds; however, the resultant lower content of n -3 long-chain ( ≥ C20) PUFA ( n -3 LC-PUFA) in fish has put their use under scrutiny. The need to investigate new oil sources exists. The present study tested the hypothesis that in Atlantic salmon ( Salmo salar L.), a high intake of stearidonic acid (SDA) from Echium oil (EO) would result in increased n -3 LC-PUFA biosynthesis due to a lower requirement for Δ6 desaturase. Comparisons were made with fish fed on diets containing rapeseed oil (RO) and FO in freshwater for 112 d followed by 96 d in seawater. EO fish had higher whole-carcass SDA and eicosatetraenoic acid (ETA) in freshwater and prolonged feeding on the EO diet in seawater resulted in higher SDA, ETA, EPA and docosapentaenoic acid (DPA) compared with RO fish. Fatty acid mass balance of freshwater fish indicated higher biosynthesis of ETA and EPA in EO fish compared with fish fed on the other diets and a twofold increase in n -3 LC-PUFA synthesis compared with RO fish. In seawater, n -3 biosynthetic activity was low, with higher biosynthesis of ETA in EO fish and appearance of all desaturated and elongated products along the n -3 pathway. SDA-enriched VO are more suitable substitutes than conventional VO from a human consumer perspective due to the resulting higher SDA content, higher total n -3 and improved n -3: n -6 ratio obtained in fish, although both VO were not as effective as FO in maintaining EPA and DHA content in Atlantic salmon.